Nickel versus Palladium in Cross-Coupling Catalysis: On the Role of Substrate Coordination to Zerovalent Metal Complexes - Cooper, Alasdair K.; Burton, Paul M.; Nelson, David J. (Synthesis, 2020)
A detailed comparison of the effect of coordinating functional groups on the performance of Suzuki–Miyaura reactions catalysed by nickel and palladium is reported, using competition experiments, robustness screening, and density functional theory calculations. Nickel can interact with a variety of functional groups, which manifests as selectivity in competitive cross-coupling reactions. The presence of these functional groups on exogenous additives has effects on cross-coupling reactions that range from a slight improvement in yield to the complete cessation of the reaction. In contrast, palladium does not interact sufficiently strongly with these functional groups to induce selectivity in cross-coupling reactions; the selectivity of palladium-catalysed cross-coupling reactions is predominantly governed by aryl halide electronic properties.
Keywords: nickel catalysis; cross-coupling; robustness screening; reaction mechanisms; structure–activity relationships